2020
DOI: 10.1097/cad.0000000000000938
|View full text |Cite
|
Sign up to set email alerts
|

The immunocytokine L19-TNF eradicates sarcomas in combination with chemotherapy agents or with immune check-point inhibitors

Abstract: Antibody-cytokine fusion proteins (also called ‘immunocytokines’) represent an emerging class of biopharmaceutical products, which are being considered for cancer immunotherapy. When used as single agents, pro-inflammatory immunocytokines are rarely capable of inducing complete and durable cancer regression in mouse models and in patients. However, the combination treatment with conventional chemotherapy or with other immune-stimulatory agents typically increases the therapeutic efficacy of immunocytokines. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Another chemotherapeutic, decarbazine, as a single agent was capable of eradicating tumors in three out of four mice, but while administered with L19-mTNF, the number of complete responses increased to four of four. Very similar synergistic effects were observed for L19-mTNF and anti-PD-1 antibody [ 101 ]. Anti-tumor effects mediated by antibody-based TNF-α delivery could also be increased by a proper combination with other cytokines, e.g., IL-2.…”
Section: Tnf-based Immunocytokinessupporting
confidence: 68%
“…Another chemotherapeutic, decarbazine, as a single agent was capable of eradicating tumors in three out of four mice, but while administered with L19-mTNF, the number of complete responses increased to four of four. Very similar synergistic effects were observed for L19-mTNF and anti-PD-1 antibody [ 101 ]. Anti-tumor effects mediated by antibody-based TNF-α delivery could also be increased by a proper combination with other cytokines, e.g., IL-2.…”
Section: Tnf-based Immunocytokinessupporting
confidence: 68%
“…After an improved response rate of ipilimumab and L19‐TNF was demonstrated in two syngeneic murine tumor models (F9, CT23), [ 61 ] a very recent study in a BALB/c derived immunocompetent murine model of sarcoma (WEHI‐164) revealed that the combination of L19‐TNF and PD‐1 inhibition was significantly more effective than PD‐1 inhibition alone. [ 62 ] These results, if confirmed in clinical trials, will have major implications for the standard care of human cancers, including melanomas.…”
Section: Open Questions and Experimental Approaches To Take Activatiomentioning
confidence: 89%
“…EDB-FN being upregulated in tumor area experiencing neoangiogenesis, L19 contributes to concentrate IL2 in the malignant bed. 149 L19IL2/L19TNF will be administered once weekly for up to 4 weeks into all injectable lesions. Of note, this combination showed promising results in a Phase II clinical trial in patients with advanced metastatic melanoma who were not candidates to surgery ( Table 2 ).…”
Section: Cytokinesmentioning
confidence: 99%